Decrease in incidence of sexually transmitted infections symptoms in men who have sex with men enrolled in a quarterly HIV prevention and care programme in West Africa (CohMSM ANRS 12324—Expertise France). (22nd March 2021) - Yaya, Issifou; Diallo, Fodié; Kouamé, Malan Jean-Baptiste; Agboyibor, Mawuényégan Kouamivi; Traoré, Issa; Coulibaly, Alou; Maiga, Kader; Mora, Marion; Palvadeau, Pamela; Dah, Elias Ter Tiero; Mensah, Ephrem; Anoma, Camille; et al.
Abstract : Objective: Although men who have sex with men (MSM) are at high risk of STI, their access to tailored healthcare services remains limited in West Africa. We assessed the change in STI symptoms incidence over time among MSM enrolled in a quarterly HIV prevention and care programme in four cities in Burkina Faso, Côte d'Ivoire, Mali and Togo. Methods: We performed a prospective cohort study in MSM followed up between 2015 and 2019. Men aged over 18 who reported anal sex with another man within the previous 3 months were offered quarterly syndromic diagnosis and treatment for STI, as well as HIV testing, peer-led counselling and support. Condoms and lubricants were also provided. The change in STI symptoms incidence during follow-up was investigated using a non-parametric trend test and mixed-effect Poisson regression models. Results: 816 participants were followed for a total duration of 1479 person-years. 198 participants (24.3%) had at least one STI symptom during follow-up. Overall, STI symptoms incidence was 20.4 per 100 person-years (95% CI 18.4 to 22.6), ranging from 15.3 in Abidjan to 33.1 in Ouagadougou (adjusted incidence rate ratio (aIRR) 2.39, 95% CI 1.55 to 3.69, p<0.001). STI symptoms incidence was 16.8 and 23.0 per 100 person-years in HIV-positive and HIV-negative participants, respectively (aIRR 0.77, 95% CI 0.57 to 1.04, p=0.087). STI symptoms incidence decreased significantly from 29.9 per 100 person-years in the first 6 months to 8.6 at 30–35 months of follow-up (aIRR per 6-month increase 0.84, 95% CI 0.77 to 0.92, p<0.001). Conclusion: STI symptoms incidence decreased over time but the overall burden of STI appeared to be very high in MSM followed up in West Africa. STI services including counselling, diagnosis and treatment should be reinforced. Laboratory tests that allow accurate diagnosis of STI are required. Strengthening STI services will be critical for controlling the HIV and STI epidemics in this vulnerable population and in the general population. Trial registration number: NCT02626286 .